Alternative route for the preparation of Zr-doped TiO2 layers for energy and environmental applications. Issue 8 (September 2015) - Bendoni, Riccardo; Mercadelli, Elisa; Sangiorgi, Nicola; Strini, Alberto; Sangiorgi, Alex; Sanson, Alessandra
Abstract: In this study, a novel procedure for the production of Zr-doped TiO2 ceramic layers, deposited by screen-printing technique, is presented. A suitable Zr precursor (Zr(IV) 2, 4-pentanedionate) was added to the formulation of a standard TiO2 ink, in order to promote the diffusion of Zr ions directly during the sintering of the deposited layers. In order to evaluate the impact of this process on the properties of the ink, thermal and rheological analysis were done; a significant effect on the flow behavior was found, related to a relevant dispersing action of the precursor. The efficacy of the method was proved by XRD analyses, that showed the stabilization of anatase phase and crystal size at high temperature (700 °C), due to Zr doping. The properties of the films were then analyzed in order to evaluate their application as photoanodes for Dye-Sensitized Solar Cells (DSCs). The use of the Zr precursor resulted to improve the film morphology, whereas it did not affect the dye adsorption capability of the TiO2 . Electrochemical characterization pointed out increased flat band potential and density of states (DOS), the latter being potentially beneficial even for photocatalytic applications. Doped photoanodes resulted to induce a slight deterioration of the performance, pointing out the need of a more accurate optimization of the process for this application. Finally, the proposed doping method resulted effective and potentially adaptable to other dopant-semiconductor systems.